STRATEGI PEMBELAJARAN CEPAT BAHASA JEPANG DAN MANDARIN DI MARKAS RTC (RIBEN TIONGHOA CENTER) PONDOK PESANTREN MAMBAUL ULUM BATA-BATA PAMEKASAN - Ah madi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The formulation of the problem in this research are: First, how is the learning of Japanese and Mandarin at the Autonomous Agency for RTC (Riben Cina Centre) Mambaul Ulum Bata-Bata Islamic Boarding School. Second, what are the Japanese and Mandarin learning strategies at the RTC Autonomous Board of Mambaul Ulum Bata-Bata Islamic Boarding School, third, what are the supporting and inhibiting factors in the Japanese and Mandarin language learning strategies at the RTC Autonomous Agency (Riben Cina Centre) Mambaul Ulum Bata Islamic Boarding School -Brick. This study uses a qualitative approach to the type of qualitative research. The data analysis technique uses data reduction, data display/presentation, and drawing conclusions. The researcher is the key instrument, while the informants are the chairman of the autonomous body and the teaching staff. Based on the analysis of the data obtained, we can conclude that: First, learning Japanese and Mandarin at the RTC autonomous institution includes general knowledge of Japanese and Mandarin in terms of speaking, listening, writing, reading, language, lifestyle, and Japanese culture. The class will evaluate correct pronunciation and practice tone. Before getting grades, the tutor first taught them to sing each poem. Second, the Japanese and Beijing Language Learning Strategies at the Autonomous Body of RTC PP. Mambaul Ulum Bata-Bata: Direct Learning Strategies, Indirect Learning Strategies, Interactive Learning Strategies, Experiential Learning Strategies, Independent Learning Strategies. Third, one of the supporting factors for the Japanese and Mandarin learning strategies at PB RTC is the factor that supports the Japanese and Mandarin learning processes, the teacher is e-kaado media (pictures) and supports various presentation and learning strategies with strategic examples, such as strategy question and answer, use of laptops and LCD devices in PP. Mambaul Ulum is equipped with complete equipment. Rumusan masalah dalam penelitian ini yaitu: Pertama Bagaimana pembelajaran bahasa Jepang dan Mandarin di Badan Otonom RTC (Riben Tionghoa Centre) Pondok Pesantren Mambaul Ulum Bata-Bata. Kedua, Bagaimana strategi pembelajaran bahasa Jepang dan Mandarin di Badan Otonom RTC PP. Mambaul Ulum Bata-Bata, ketiga, Apa saja pendukung dan penghambat dalam strategi pembelajaran bahasa Jepang dan Mandarin di Badan Otonom RTC PP. Mambaul Ulum Bata-Bata. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kualitatif. Adapun teknik analisis datanya menggunakan reduksi data, display/penyajian data, dan kesimpulan. Peneliti sebagai instrument kunci, sedangkan informannya adalah ketua badan otonom serta staf pengajar. Berdasarkan analisis data yang diperoleh, kami dapat menyimpulkan bahwa: Pertama, belajar bahasa Jepang dan Mandarin di lembaga otonom RTC mencakup pengetahuan umum bahasa Jepang dan Mandarin baik dari segi berbicara, mendengar, menulis, membaca, bahasa dan budaya Jepang. Kedua, Strategi Pembelajaran Bahasa Jepang dan Beijing pada Badan Otonom RTC PP. Mambaul Ulum Bata-Bata: Strategi Pembelajaran Langsung dan Tidak Langsung, Interaktif, Experiential Learning, Belajar Mandirin. Ketiga, faktor pendukung strategi pembelajaran bahasa Jepang dan bahasa Mandarin di PB RTC adalah faktor yang mendukung proses pembelajaran bahasa Jepang dan bahasa Mandarin, guru adalah media e-kaado (gambar) dan mendukung berbagai strategi presentasi dan pembelajaran dengan contoh strategis, seperti s tanya jawab, penggunaan laptop dan alat LCD di PP. Mambaul Ulum dilengkapi dengan peralatan lengkap